Basic LEUCINE ZIPPER TRANSCRIPTION FACTOR67 Transactivates DELAY OF GERMINATION1 to Establish Primary Seed Dormancy in Arabidopsis. Issue 6 (8th April 2019) - Bryant, Fiona M.; Hughes, David; Hassani-Pak, Keywan; Eastmond, Peter J.
Abstract : Basic LEUCINE ZIPPER TRANSCRIPTION FACTOR67 acts downstream of LEAFY COTYLEDON1 to induce DELAY OF GERMINATION1 expression during Arabidopsis seed maturation and to establish primary dormancy. Abstract: Seed dormancy governs the timing of germination, one of the most important developmental transitions in a plant's life cycle. The DELAY OF GERMINATION1 ( DOG1 ) gene is a key regulator of seed dormancy and a major quantitative trait locus in Arabidopsis ( Arabidopsis thaliana ). DOG1 expression is under tight developmental and environmental regulation, but the transcription factors involved are not known. Here we show that basic LEUCINE ZIPPER TRANSCRIPTION FACTOR67 (bZIP67) acts downstream of the central regulator of seed development, LEAFY COTYLEDON1, to transactivate DOG1 during maturation and help to establish primary dormancy. We show that bZIP67 overexpression enhances dormancy and that bZIP67 protein (but not transcript) abundance is increased in seeds matured in cool conditions, providing a mechanism to explain how temperature regulates DOG1 expression. We also show that natural allelic variation in the DOG1 promoter affects bZIP67-dependent transactivation, providing a mechanism to explain ecotypic differences in seed dormancy that are controlled by the DOG1 locus.